The Influence of Service Quality and Price on Consumer Loyalty at Mie Gacoan Pancing (Case Study of Management Study Program Students at UNIMED) - Putra, Irwansyah Putra; Monalisa, Indah; Nasution, Risky Alhaq; Rinaldi, Muammar; Sienny (Outline Journal of Management and Accounting, 2025)
This study aims to analyze the influence of service quality and price on consumer loyalty at Mie Gacoan Pancing. The research method used is quantitative with a multiple linear regression approach. Data were collected through a questionnaire that has been tested for validity and reliability. The results show that service quality has a positive and significant effect on consumer loyalty, while price has no significant effect. Simultaneously, both independent variables have a significant effect on consumer loyalty with a contribution of 50.4%. The implication of this study is that the management of Mie Gacoan Pancing should further improve service quality to increase customer loyalty.